If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2 (2r + 5) + 1 = 5-3(3-r)
We simplify the equation to the form, which is simple to understand
2(2r+5)+1=5-3(3-r)
Reorder the terms in parentheses
+(+4r+10)+1=5-3*(3-r)
Remove unnecessary parentheses
+4r+10+1=+5-3+*(+3-r+)
Reorder the terms in parentheses
+4r+10+1=5+(-9+3r)
Remove unnecessary parentheses
+4r+10+1=+5-9+3r
We move all terms containing r to the left and all other terms to the right.
+4r-3r=+5-9-10-1
We simplify left and right side of the equation.
+1r=-15
We divide both sides of the equation by 1 to get r.
r=-15
| 4(x-1)=2(x+2)-x | | 5v=-2v-3v | | -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w | | 5.8-1.4=16 | | 9(g+2)-4=7g+3(3g+8) | | 7(st)=(7s)t | | 5w+a=4.8+8w | | -(3b-15)=6(2hb+5) | | -4m-23=5 | | 2y=-5x+12 | | 5w+9=4.8+8w | | 25+5x=-80-2x | | -4.9t^2+355t+87=0 | | 22(2y+1)= | | 2x+2(2x+8)=772 |